Preparation process of high-purity magnesium silicate
By adding magnesium sulfate and sodium silicate solutions dropwise and heating the solution, the problem of slow precipitation doping and filtration speed in the preparation of magnesium silicate by precipitation method is solved, and the purity and adsorption of magnesium silicate is improved, which is suitable for food and Applications in the field of medicine.
Patent Information
- Application Number
- CN202411208498.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-08-30
AI Technical Summary
Magnesium silicate prepared by precipitation method has problems with coprecipitation doping and slow filtration speed, which affects its purity and usage performance, and requires higher purity and safety, especially in applications in the food and pharmaceutical fields.
By adding magnesium sulfate solution and sodium silicate solution to the urea solution in a certain proportion, heating and stirring, the pH of the solution gradually increases, thereby accelerating the formation of magnesium silicate, reducing the probability of impurities co-precipitation, and increasing the The purity of magnesium silicate.
It effectively reduces the impurity content in magnesium silicate, improves its purity and filtration, enhances adsorption, simplifies the process flow and reduces energy consumption, and is suitable for industrial production.
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation technology of magnesium silicate, and more specifically to a preparation technology of high-purity magnesium silicate. Background Art
[0002] Magnesium silicate is already a mature chemical product, which is widely used in medicine, food, environment and other fields, and is closely related to human life; therefore, the safety of magnesium silicate has become particularly important, and the most concerning safety factor is the purity of magnesium silicate.
[0003] There are two main methods for preparing magnesium silicate today, namely precipitation method and hydrothermal method. Since the equipment and conditions required for the hydrothermal reaction are more demanding than those for the precipitation method, the precipitation method is usually used to produce magnesium silicate on the market. However, magnesium silicate produced by the precipitation method may contain a certain amount of impurities, which will affect the performance and safety of magnesium silicate, especially in food (for magnesium silicate used in the food field, the provisions of GB 1886.62-2015, i.e., the "National Food Safety Standard for Food Additive Magnesium Silicate") and pharmaceutical applications. The high BET specific surface area of magnesium silicate gives it better fluidity and anti-caking properties, while providing more adsorption sites, enhancing its anti-caking and adsorption properties in the food or pharmaceutical fields.
[0004] The coprecipitation phenomenon refers to the precipitation of certain coexisting soluble substances when the precipitate is precipitated from the solution, which will affect the purity of the precipitate and cause the precipitate to form fine particles. These fine particles may clog the filter, making filtration difficult. The main reasons for this phenomenon include surface adsorption, mixed crystals or embedding. Magnesium silicate itself is an adsorbent with strong adsorption capacity, and its coprecipitation phenomenon is more obvious, especially the coprecipitation caused by embedding. The embedding phenomenon refers to the coprecipitation caused by the fast precipitation speed, the impurities or mother liquor adsorbed on the surface of the precipitate have no time to leave, and are covered by the subsequently grown precipitate, thus being hidden inside the precipitate.
[0005] In order to solve this problem, a Chinese patent with publication number CN2021109976832 published on March 21, 2023 discloses a preparation method and application of a magnesium silicate adsorbent. This scheme reduces the adsorption on the surface of magnesium silicate by washing the filter cake with water, but the removal effect on embedded and mixed crystals is general.
[0006] Therefore, it is necessary to provide a preparation process of magnesium silicate, which can solve the co-precipitation doping problem and the slow filtration speed problem caused by the precipitation method for synthesizing magnesium silicate. Summary of the invention
[0007] In view of the problems existing in the prior art, the object of the present invention is to provide a preparation process of high-purity magnesium silicate. The technical scheme comprises the following steps: adding magnesium sulfate solution and sodium silicate solution to a urea solution in a certain proportion, heating and stirring the solution, so that the pH value of the solution gradually increases, thereby gradually accelerating the formation rate of magnesium silicate, reducing the probability of co-precipitation of impurities, and thus improving the purity of magnesium silicate.
[0008] To solve the above problems, the present invention adopts the following technical solutions.
[0009] A preparation process of high-purity magnesium silicate, including the following preparation process of magnesium silicate: S1: respectively prepare a magnesium sulfate solution with a mass concentration of 14%-25% and a sodium silicate solution with a mass concentration of 33%-35%; S2: Add 200-300g of water into the reactor, then add urea in a ratio of water: urea = 20-30:1, and stir to mix to form a urea solution; S3: slowly dropwise add the sodium silicate solution and magnesium sulfate solution prepared in step S1 to the reactor in step S2 in a ratio of n(Si):n(Mg)=5-6:1, stirring and heating at the same time, and after the dropwise addition is completed, heat-insulate, age, filter and collect the filter cake; S4: The filter cake in step S3 is washed and dried to obtain a finished product.
[0010] Furthermore, in the step S1, the content of sodium silicate is sodium oxide ≥ 15%, and silicon dioxide ≥ 30%; the content of magnesium oxide in magnesium sulfate is 4-6%.
[0011] Furthermore, the mass concentration of the urea solution in step S2 is 3%-5%.
[0012] Furthermore, in the step S3, the dropping speed of the sodium silicate solution and the magnesium sulfate solution is 6.67-10 mL / min.
[0013] Furthermore, in step S3, heating is performed until the solution boils.
[0014] Furthermore, the heat preservation and aging time in the step S3 is 1-2 hours.
[0015] Furthermore, the filtration time in the S3 step is 13-15 minutes.
[0016] Furthermore, the flushing operation in the step S4 is to use a washing liquid to flush the filter cake and collect the flushing liquid; and use the washing liquid to flush until the flushing liquid is mixed with the barium chloride solution and is no longer turbid.
[0017] Furthermore, the washing liquid is deionized water.
[0018] Furthermore, in the step S4, the drying temperature is 60-80° C., and the drying time is 36-72 hours.
[0019] Compared with the prior art, the advantages of the present invention are: 1. This scheme slowly drops sodium silicate solution and magnesium sulfate solution into urea solution. The pH of the initial urea solution is neutral, and the reaction is not activated at this time. When the urea solution is heated, urea begins to decompose to generate ammonia and carbon dioxide. This decomposition process causes the pH of the solution to gradually increase. When the pH is greater than 7, the reaction of sodium silicate and magnesium sulfate is activated to generate magnesium silicate; the carbon dioxide generated by the decomposition of urea helps to improve the mixing uniformity of the solution and effectively prevents incomplete or uneven reactions. As the heating process continues, the pH value of the solution increases further, which not only promotes the decomposition of urea, but also accelerates the formation reaction of magnesium silicate, which helps to reduce impurity doping during the coprecipitation process. In addition, the drop rate of the magnesium silicate solution and the sulfuric acid solution is controlled at 6.67-10 mL / min to ensure the uniformity and efficiency of the reaction, thereby obtaining high-purity magnesium silicate.
[0020] Second, this solution adds sodium silicate solution and magnesium sulfate solution to urea solution in a ratio of n(Si):n(Mg)=5-6:1, and heats and stirs during the addition. This operation can ensure a more complete reaction, thereby improving the purity of magnesium silicate. At the same time, the magnesium silicate prepared by this method has good filterability and adsorption. DETAILED DESCRIPTION
[0021] The present invention will be further described below: Embodiment 1:
[0022] Magnesium sulfate with a magnesium oxide content of 5% was added with water to prepare a magnesium sulfate solution with a mass concentration of 18.97%; sodium silicate with a sodium oxide content of 16% and a silicon dioxide content of 31% was added with water to prepare a sodium silicate solution with a mass concentration of 34.15%. 200g of water and 10g of urea were added to a 500ml three-necked flask and stirred until uniformly mixed to obtain a urea solution with a mass concentration of 4.76%. Subsequently, the prepared sodium silicate solution and magnesium sulfate solution were dripped into the urea solution at a rate of 6.67mL / min in a ratio of n(Si):n(Mg)=6:1. When the dripping began, the agitator was turned on and the heater was turned on to heat the solution until it boiled. After the dripping was completed, the mixture was kept warm at 100℃ for 2h, and the filter cake was collected after filtering for 15min. The filter cake was rinsed with deionized water until the washing solution was no longer turbid when mixed with the barium chloride solution to obtain a wet magnesium silicate product. The obtained wet magnesium silicate product was dried at 70℃ for 36h to obtain a finished product.
[0023] Embodiment 2:
[0024] Magnesium sulfate with a magnesium oxide content of 5.89% was added with water to prepare a magnesium sulfate solution with a mass concentration of 24.84%; sodium silicate with a sodium oxide content of 16% and a silicon dioxide content of 30% was added with water to prepare a sodium silicate solution with a mass concentration of 31.3%. 250g of water and 10g of urea were added to a 500ml three-necked flask and stirred until uniformly mixed to obtain a urea solution with a mass concentration of 3.85%. Subsequently, the prepared sodium silicate and magnesium sulfate were dripped into the urea solution at a rate of 6.67mL / min in a ratio of n(Si):n(Mg)=5.5:1. When the dripping began, the stirrer was turned on and the heater was turned on to heat the solution until it boiled. After the dripping was completed, it was kept warm at 100℃ for 1h, and the filter cake was collected after filtering for 15min. The filter cake was rinsed with deionized water until the washing liquid and the barium chloride solution were no longer turbid, and a wet magnesium silicate product was obtained. The obtained wet magnesium silicate product was dried at 70° C. for 48 hours to obtain a finished product.
[0025] Embodiment 3:
[0026] Magnesium sulfate with a magnesium oxide content of 4.5% was added with water to prepare a magnesium sulfate solution with a mass concentration of 22.51; sodium silicate with a sodium oxide content of 15% and a silicon dioxide content of 33% was added with water to prepare a sodium silicate solution with a mass concentration of 30.69%. 300g of water and 10g of urea were added to a 500ml three-necked flask and stirred until uniformly mixed to obtain a urea solution with a mass concentration of 3.23%. Subsequently, the prepared sodium silicate and magnesium sulfate were dripped into the urea solution at a rate of 6.67mL / min in a ratio of n(Si):n(Mg)=5:1. When the dripping began, the stirrer was turned on and the heater was turned on to heat the solution until it boiled. After the dripping was completed, it was kept warm at 100℃ for 1h, and the filter cake was collected after filtering for 15min. The filter cake was rinsed with deionized water until the washing liquid was mixed with the barium chloride solution and was no longer turbid, and a wet magnesium silicate product was obtained. The obtained wet magnesium silicate product was dried at 80℃ for 72h to obtain a finished product.
[0027] Embodiment 4:
[0028] Magnesium sulfate with a magnesium oxide content of 4.5% was added with water to prepare a magnesium sulfate solution with a mass concentration of 22.51; sodium silicate with a sodium oxide content of 15% and a silicon dioxide content of 33% was added with water to prepare a sodium silicate solution with a mass concentration of 30.69%. 300g of water and 10g of urea were added to a 500ml three-necked flask and stirred until uniformly mixed to obtain a urea solution with a mass concentration of 3.23%. Subsequently, the prepared sodium silicate and magnesium sulfate were dripped into the urea solution at a rate of 10mL / min in a ratio of n(Si):n(Mg)=5:1. When the dripping began, the stirrer was turned on and the heater was turned on to heat the solution until it boiled. After the dripping was completed, it was kept warm at 100℃ for 1h, and the filter cake was collected after filtering for 15min. The filter cake was rinsed with deionized water until the washing liquid was mixed with the barium chloride solution and was no longer turbid, and a wet magnesium silicate product was obtained. The obtained wet magnesium silicate product was dried at 80℃ for 72h to obtain a finished product.
[0029] Embodiment 5:
[0030] Magnesium sulfate with a magnesium oxide content of 4.5% was added with water to prepare a magnesium sulfate solution with a mass concentration of 22.51; sodium silicate with a sodium oxide content of 15% and a silicon dioxide content of 33% was added with water to prepare a sodium silicate solution with a mass concentration of 30.69%. 300g of water and 10g of urea were added to a 500ml three-necked flask and stirred until uniformly mixed to obtain a urea solution with a mass concentration of 3.23%. Subsequently, the prepared sodium silicate and magnesium sulfate were dripped into the urea solution at a rate of 8.52mL / min in a ratio of n(Si):n(Mg)=5:1. When the dripping began, the stirrer was turned on and the heater was turned on to heat the solution until it boiled. After the dripping was completed, the mixture was kept warm at 100℃ for 1h, and the filter cake was collected after filtering for 15min. The filter cake was rinsed with deionized water until the washing solution was no longer turbid when mixed with the barium chloride solution to obtain a wet magnesium silicate product. The obtained wet magnesium silicate product was dried at 80℃ for 72h to obtain a finished product.
[0031] Comparative Example 1: Magnesium sulfate with a magnesium oxide content of 5% was added with water to prepare a magnesium sulfate solution with a mass concentration of 18.97%; sodium silicate with a sodium oxide content of 16% and a silicon dioxide content of 31% was added with water to prepare a sodium silicate solution with a mass concentration of 34.15%. 100g of water was added to a 500ml three-necked flask. Subsequently, the prepared sodium silicate and magnesium sulfate were dripped into the water at a rate of 6.67mL / min according to the ratio of n(Si):n(Mg)=5:1. When the dripping began, the agitator was turned on and 1M sodium hydroxide was dripped at the same time. After the dripping was completed, it was kept warm at 100℃ for 2h, and the filter cake was collected after filtering for 33min. The filter cake was rinsed with water until the washing liquid was mixed with the barium chloride solution and was no longer turbid, and a wet magnesium silicate product was obtained. The obtained wet magnesium silicate product was dried at 80℃ for 72h to obtain a finished product.
[0032] Comparative Example 2: Magnesium sulfate with a magnesium oxide content of 5% was added with water to prepare a magnesium sulfate solution with a mass concentration of 24.84%; sodium silicate with a sodium oxide content of 16% and a silicon dioxide content of 30% was added with water to prepare a sodium silicate solution with a mass concentration of 31.3%. 50g of water was added to a 500ml three-necked flask. Subsequently, the prepared sodium silicate and magnesium sulfate were dripped into the water at a rate of 6.67mL / min in a ratio of n(Si):n(Mg)=5.5:1. When the dripping began, the agitator was turned on and 1M sodium hydroxide was dripped at the same time. After the dripping was completed, the mixture was kept warm at 100℃ for 1h, and the filter cake was collected after filtering for 40min. The filter cake was rinsed with water until the washing liquid was no longer turbid when mixed with the barium chloride solution to obtain a wet magnesium silicate product. The obtained wet magnesium silicate product was dried at 70℃ for 48h to obtain a finished product.
[0033] Comparative Example 3: Magnesium sulfate with a magnesium oxide content of 5% was added with water to prepare a magnesium sulfate solution with a mass concentration of 22.3%; sodium silicate with a sodium oxide content of 16% and a silicon dioxide content of 30% was added with water to prepare a sodium silicate solution with a mass concentration of 30.12%. 100g of water and 0.4g of sodium hydroxide were added to a 500ml three-necked flask and stirred to prepare a sodium hydroxide solution with a mass concentration of 0.4%. Subsequently, the prepared sodium silicate and magnesium sulfate were dripped into the sodium hydroxide solution at a rate of 6.67mL / min according to the ratio of n(Si):n(Mg)=5.5:1. When the dripping began, the agitator was turned on. After the dripping was completed, it was kept warm at 100℃ for 1h, and the filter cake was collected after filtering for 33min. The filter cake was rinsed with water until the washing liquid was mixed with the barium chloride solution and was no longer turbid, and a wet magnesium silicate product was obtained. The obtained wet magnesium silicate product was dried at 60℃ for 36h to obtain a finished product.
[0034] Comparative Example 4 Add 50ml of water, 0.4g (1.6mmol) of Mg(NO3)2·6H2O and urea to a 500ml three-necked flask, and stir to obtain a mixed solution. Add 100g of magnesium sulfate to the mixed solution and ultrasonically treat for 20min. Then transfer all the solution and solid after ultrasonic treatment to a 0.7ml hydrothermal reactor, heat to 100℃, keep warm for 5h, filter, and collect the solid. Weigh a certain amount of sodium silicate to prepare a sodium silicate solution with a mass concentration of 27% (0.7mmol). Put the sodium silicate solution and solid together in a 70ml hydrothermal reactor, heat to 160℃, keep warm for 8h, cool to room temperature, wash with deionized water several times, and dry at 80℃ for 30min to obtain the finished product.
[0035] Experimental Example 1 The magnesium silicate content of the magnesium silicate prepared in the examples and comparative examples of the present invention was analyzed, and the specific analysis results are shown in Table 1.
[0036] Table 1 Analysis results of the content of magnesium silicate prepared in the examples and comparative examples ; It can be seen from Examples 1 to 3 and Comparative Examples 1 to 3 that when sodium silicate and magnesium sulfate are added dropwise to a urea solution of water: urea = 20-30:1 at a ratio of n(Si):n(Mg)=5-6:1, not only can the time required for the filtration step be significantly reduced, but other impurities in magnesium silicate can also be effectively controlled to below 0.6%, thereby improving the overall purity of the product; while the impurities in conventional methods are generally 3-5% or even higher. Therefore, this method can effectively reduce the impurities in the generated magnesium silicate, and the operation method of this solution is simple, energy consumption is low, and the yield is high in industrial production.
[0037] It can be seen from Examples 1 to 3 and Comparative Example 4 that the magnesium silicate prepared by the method provided in this scheme has a lower impurity content and a higher magnesium oxide content than the magnesium silicate prepared by the hydrothermal method in Comparative Example 4. Since the adsorption of magnesium silicate depends on the content of magnesium oxide, when the magnesium oxide content of magnesium silicate is high, the adsorption effect of magnesium silicate is better. Therefore, the adsorption effect of magnesium silicate prepared in Comparative Example 4 is significantly lower than the adsorption effect of magnesium silicate prepared in Example.
[0038] From Example 1, Example 4, and Example 5, it can be seen that: when the dropping rate is 6.67 mL / min, the impurity content of magnesium silicate is the lowest, and the magnesium oxide content is the highest; when the dropping rate is lower than 6.67 mL / min or higher than 10 mL / min, the impurity content of magnesium silicate will increase significantly, and the content of magnesium oxide in magnesium silicate will decrease significantly, thereby affecting the adsorption effect of magnesium silicate.
[0039] Experimental Example 2: The magnesium silicate prepared in the examples of the present invention and the comparative examples was subjected to performance tests, and the specific results are shown in Table 2: Table 2 Performance test results of magnesium silicate prepared in Examples and Comparative Examples ; From the data in Table 2, it can be seen that the process provided by the present invention not only significantly improves the yield of the product, making the yield reach more than 93%, but also increases the BET specific surface area of magnesium silicate, thereby improving the adsorption effect of magnesium silicate particles. In addition, the present method shortens the filtration time during the preparation process, so that the process can be promoted in industrial preparation.
[0040] It can be seen from Examples 3 to 5 that: when other conditions remain unchanged, it can be seen from Example 3 that when the dropping rate is 6.67 mL / min, the impurity content of magnesium silicate is 0.50%, and the BET specific surface area is 323.00 m² / g; it can be seen from Example 5 that when the dropping rate is 8.52 mL / min, the impurity content of magnesium silicate is 0.49%, and the BET specific surface area is 357.00 m² / g; it can be seen from Example 4 that when the dropping rate is 10 mL / min, the impurity content of magnesium silicate is 0.53%, and the BET specific surface area is 313.00 m² / g; therefore, the optimal dropping rate is 6.67 mL / min.
Claims
1. A preparation process of high-purity magnesium silicate, characterized in that: The preparation process of magnesium silicate is as follows: S1: respectively prepare a magnesium sulfate solution with a mass concentration of 14%-25% and a sodium silicate solution with a mass concentration of 33%-35%; S2: Add 200-300g of water into the reactor, then add urea in a ratio of water: urea = 20-30:1, and stir to mix to form a urea solution; S3: slowly dropwise add the sodium silicate solution and magnesium sulfate solution prepared in step S1 to the reactor in step S2 in a ratio of n(Si):n(Mg)=5-6:1, stirring and heating at the same time, and after the dropwise addition is completed, heat-insulate, age, filter and collect the filter cake; S4: The filter cake in step S3 is washed and dried to obtain a finished product.
2. A process for preparing high-purity magnesium silicate according to claim 1, characterized in that: In the step S1, the content of sodium silicate is sodium oxide ≥ 15%, and silicon dioxide ≥ 30%; the content of magnesium oxide in magnesium sulfate is 4-6%.
3. A process for preparing high-purity magnesium silicate according to claim 1, characterized in that: The mass concentration of the urea solution in step S2 is 3%-5%.
4. A process for preparing high-purity magnesium silicate according to claim 1, characterized in that: In the step S3, the dropping speed of the sodium silicate solution and the magnesium sulfate solution is 6.67-10 mL / min.
5. A process for preparing high-purity magnesium silicate according to claim 1, characterized in that: In the step S3, the solution is heated until boiling.
6. A process for preparing high-purity magnesium silicate according to claim 1, characterized in that: The heat preservation and aging time in the step S3 is 1-2 hours.
7. A process for preparing high-purity magnesium silicate according to claim 1, characterized in that: The filtration time in the S3 step is 13-15 minutes.
8. A process for preparing high-purity magnesium silicate according to claim 1, characterized in that: The washing operation in step S4 is to use a washing liquid to wash the filter cake and collect the washed liquid; and use the washing liquid to wash until the washed liquid is mixed with the barium chloride solution and is no longer turbid.
9. A process for preparing high-purity magnesium silicate according to claim 8, characterized in that: The washing liquid is deionized water.
10. A process for preparing high-purity magnesium silicate according to claim 1, characterized in that: In the step S4, the drying temperature is 60-80° C. and the drying time is 36-72 hours.
Citation Information
Patent Citations
Copper chromite black pigment, and preparation method and application thereof
CN103708555A
Preparation method of magnesium silicate / carbon composite material
CN103933938A
Porous magnesium silicate composite adsorption film and preparation method thereof
CN108067182A
Low-viscosity magnesium silicate, a magnesium silicate derivative thereof, and production method of low-viscosity magnesium silicate and derivative
CN110627076A
Preparation method and application of mesoporous magnesium silicate
CN110980750A